Interpretation of lineaments and faults near Summerville, South Carolina, USA, using LiDAR data: implications for the cause of the 1886 Charleston, South Carolina, earthquake - Marple, Ronald T.; Hurd, James D. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2020)
LiDAR (light detection and ranging) data acquired near Summerville, South Carolina, reveal numerouslineaments trending in various directions across the Middleton Place-Summerville seismic zone (MPSSZ) andsurrounding area. These lineaments are defined by linear depressions and stream valleys that are developed withinlate Eocene to Holocene marine, marginal marine, and fluvial sediments of the Atlantic Coastal Plain. The 40-kmlong,ENE-WSW-oriented Deer Park lineament coincides with the Woodstock epicenter of the 1886 Charlestonearthquake, suggesting that the main shock may have occurred along a fault associated with this lineament. Theproximity of the 17-km-long, ENE-WSW-oriented Middleton Place lineament to the Middleton Place epicentersuggests that it too may have ruptured in 1886. Several E-W-oriented topographic scarps are also located nearthe area of modern seismicity, including the 3- to 5-km-long, south-facing McChune and Summerwood scarps.The McChune scarp is aligned with the E-W-trending portion of the Summerville scarp to the west, suggestingthat both scarps may be from uplift to the north along the same fault. The McChune scarp and the Otranto andMiddleton Place lineaments coincide with faults interpreted from previously acquired seismic-reflection profiles,suggesting that these features are surface expressions of Quaternary faults. Other lineaments east of the MPSSZare associated with Neogene structural domes, indicating that the interpreted faults along these lineaments havebeen active during the late Cenozoic. The LiDAR data also revealed a ~350-m dextral offset of a mid-Pleistocenebeach ridge along the Woodstock fault and a ~20-km-long, NW-SE-oriented lineament to the east (Canterhilllineament) that appears to be the surface expression of the Charleston fault.